(untitled) (Journal of Asian Geography, 2026)
Watersheds in the Philippines are increasingly vulnerable to geohazards such as soil erosion, driven by land-use change and climate-intensified rainfall. This degradation threatens both ecosystem stability and downstream communities. To better understand the extent of erosion in a watershed in the southern Philippines, this study presents a hazard assessment framework using the Revised Universal Soil Loss Equation (RUSLE), integrated within a Geographic Information System (GIS), to quantify and map soil erosion risk in the Bubunawan River Watershed (BRW) in Bukidnon, a key tributary of the Cagayan de Oro River Basin. By processing spatially distributed parameters, namely rainfall erosivity (R), soil erodibility (K), topographic factor (LS), cover management (C), and conservation practices (P), the model estimated a mean annual soil loss of 246.50 tonnes per hectare per year. The analysis identified high-hazard zones, revealing that 21.66% of the watershed exhibits very high to extreme erosion susceptibility, thus requiring priority intervention. Scenario-based modelling further elucidated system dynamics. Simulation of potential soil loss (7,524.70 t/ha/yr) under conditions without land cover and conservation practices effectively isolates and quantifies the mitigating role of current management strategies. Additionally, simulations of future climate scenarios with rainfall increases of 10–20% indicate elevated erosion rates. In contrast, modelling of nature-based solutions, specifically the reforestation of rangelands, demonstrates a potential reduction in soil loss of 33.27%. This research presents a replicable approach for transforming geospatial data into actionable insights for hazard mitigation, providing a critical tool for sustainable watershed management and enhancing resilience to climate-related geohazards.